Long period grating based toluene sensor for use with water contamination - Partridge, Matthew; Wong, Rebecca; James, Stephen W.; Davis, Frank; Higson, Seamus P. J.; Tatam, Ralph P. (Elsevier Science B.V., Amsterdam., 2014)
A demonstration of the use of a calix[4]resorcinarene coated optical fibre long period grating sensor for the detection of toluene in water is presented. Monitoring water quality both for domestic use and around industrial sites is critical to the preservation of clean water provision. Here we show that, by using a fibre optic based sensor system, water quality monitoring can be carried out without the requirement for water sampling or pre-concentration. The results presented demonstrate that this proof-of-concept sensor is capable of sensing ∼100ppm concentrations of toluene with semi-selectivity and low (<10ppm) variation.